Exploring dataflow testing of arrays - Hamlet, D.; Gifford, B.; Nikolik, B. (Proceedings of 1993 15th International Conference on Software Engineering, 1993)
A scheme is presented for constructing prototype testing tools to experiment with issues in data-flow testing of arrays. Data-flow testing is a variant of path testing that falls between the extremes of simple run-time instrumentation, and full path testing. In data-flow testing, the paths selected for exercising are variants of def/use (DU) paths for program variables. Tool support for data-flow testing takes the form of static program analysis followed by run-time instrumentation. The output from a test analyzer is a list of untested, possible DU associations. With the novel approach to constructing testing-supporting tools, it is easy to experiment with new analysis methods. The authors describe the implementation of a DU-path analyzer as an example of this approach. Using the prototype tool, experiments and issues are considered raised by an analyzer that treats arrays differently from existing tools. Each array element is considered to be a distinct data-flow object.< >